Strategi Komunikasi Dakwah Kajian Keluarga Berbasis Online: Studi di Masjid Al Irsyad Surabaya - Herma Musyanto, Moch.; Masrur Huda (Kartika: Jurnal Studi Keislaman, 2025)
The rapid advancement of digital technology has transformed the pattern of Islamic preaching (dakwah) communication from traditional approaches to online-based platforms. This study aims to analyze the dakwah communication strategies implemented in the Kajian Keluarga Online program at Al Irsyad Mosque, Surabaya, focusing on the effectiveness of the marketing communication mix in reaching and maintaining audience engagement. Using a qualitative approach with a case study design, data were collected through in-depth interviews with mosque administrators, media managers, and active participants, supported by observation and digital documentation. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, display, and conclusion drawing. The findings indicate that the dakwah communication strategy at Al Irsyad Mosque effectively integrates elements of advertising, public relations, direct promotion, and social media marketing. The utilization of Zoom and social media platforms, particularly Instagram and YouTube, successfully expands audience reach and enhances participant loyalty. This study highlights that innovative, technology-based dakwah communication can strengthen the mosque’s role as a center for Muslim family development that is adaptive to the dynamics of the digital era.